Properties of Sediment Trap Catchment Areas in Fram Strait: Results From Lagrangian Modeling and Remote Sensing - Wekerle, Claudia; Krumpen, Thomas; Dinter, Tilman; von Appen, Wilken-Jon; Iversen, Morten Hvitfeldt; Salter, Ian (Frontiers in Marine Science, 2018)
Vertical particle fluxes are responsible for the transport of carbon and biogenic material from the surface to the deep ocean, hence understanding these particle fluxes is of climate relevance. Sediment traps operated in Fram Strait in the framework of the Arctic long-term observatory FRAM provide an estimate of vertical particle fluxes in a region of high CO2 uptake. Until now the source area (catchment area) of trapped particles is unclear; however, lateral advection of particles is supposed to play an important role. This study presents a Lagrangian method to backtrack the origin of particles for two Fram Strait moorings equipped with sediment traps in 200 m and 2300 m depth by using the time-dependent velocity field of a high-resolution, eddy-resolving ocean-sea ice model. Our study shows that the extent of the catchment area is larger the deeper the trap and the slower the settling velocity. Chlorophyll-a concentration as well as sea ice coverage of the catchment area are highest in the summer months. The high sea ice coverage in summer compared to winter can possibly be related to a weaker across-strait sea level pressure difference, which allows more sea ice to enter the then well-stratified central Fram Strait where moorings are located. Hence, highest vertical particle fluxes may be expected in late summer and autumn. Furthermore, a backward sea ice tracking approach shows that the origin and age of sea ice drifting through Fram Strait, partly responsible for vertical particle fluxes, varies strongly from year to year, pointing to a high variability in the composition of particles trapped in the moorings.